2017
DOI: 10.1038/ja.2017.104
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-regulating protease Atg4: structure, function, regulation and inhibition

Abstract: Autophagy is an intracellular degradation system that contributes to cellular homeostasis through degradation of various targets such as proteins, organelles and microbes. Since autophagy is related to various diseases such as infection, neurodegenerative diseases and cancer, it is attracting attention as a new therapeutic target. Autophagy is mediated by dozens of autophagy-related (Atg) proteins, among which Atg4 is the sole protease that regulates autophagy through the processing and deconjugating of Atg8. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 71 publications
2
95
0
Order By: Relevance
“…Atg4 is a cysteine protease of Clan CA and family C54 that is a crucial for both Atg8-PE conjugation and subsequent delipidation [61]. Atg4 was first identified in yeast by Lang et al [46], who demonstrated that this protein was essential for the process of delivering the autophagic vesicles to the vacuole lumen in S. cerevisiae.…”
Section: Discussionmentioning
confidence: 99%
“…Atg4 is a cysteine protease of Clan CA and family C54 that is a crucial for both Atg8-PE conjugation and subsequent delipidation [61]. Atg4 was first identified in yeast by Lang et al [46], who demonstrated that this protein was essential for the process of delivering the autophagic vesicles to the vacuole lumen in S. cerevisiae.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter, the inhibition is produced by the formation of a disulfide bond and very low redox potentials are required for its activation, which is mediated by the cytosolic thioredoxin TRXh1 [118]. The importance of a functional ATG4 in autophagy is supported by data showing that when ATG4 activity is increased by either phosphorylation or glycosylation, autophagy is activated, and when it is reduced by ubiquitination autophagy is inhibited [119].…”
Section: Ros Levelsmentioning
confidence: 99%
“…Redox conditions within mammalian cells have been shown to directly regulate the activity of autophagy core proteins, including the cysteine protease ATG4 and the autophagy receptor p62 (160,195). In mammals, four homologs of ATG4 with distinct cysteine protease activities have been identified: ATG4A/ autophagin-2, ATG4B/autophagin-1, ATG4C/autophagin-3, and ATG4D/autophagin-4 (139). ATG4 catalyzes cleavage of LC3 to expose a COOH-terminal glycine residue that ultimately leads to conjugation with PE (LC3-II-PE).…”
Section: Autophagy and Oxidant Exposurementioning
confidence: 99%